Analysis of tourism carrying capacity at KSPP Tanjung Lesung as part of sustainable marine tourism development - Laksana, April; Huda, Miftahul; Kenedi, Kenedi (Jurnal Teknika, 2023)
Marine tourism is one of the tourism sectors with significant potential for development in the province of Banten. However, the development of this sector must be carried out with consideration for the principles of sustainable development. In the context of marine tourism, the assessment of tourism carrying capacity becomes crucial as marine tourist attractions are prone to environmental damage and social issues. Tourism carrying capacity assessment (TCCA) is one approach that can be used to evaluate how many tourists visits a destination can handle without harming the environment or reducing the quality of the tourist experience. TCCA analysis is conducted by considering aspects such as economic facilities, socio-cultural, and ecological environment. This research aims to assess the tourism carrying capacity at Tanjung Lesung Tourism Special Economic Zone as part of sustainable marine tourism development, based on which supporting aspects need to be developed and to determine the coupling coordination among these three aspects. The aspect that needs development is the ecological environmental aspect with a performance level of 8.79%. Meanwhile, the lowest degree of coordination relationship among systems that needs improvement is the relationship between socio-cultural and ecological environmental aspects, with a degree value of 0.64899.